Comparison of efficacy of dental varnish containing fluoride either with CPP-ACP or bioglass on root caries: Ex vivo study. (June 2018) - Sleibi, A.; Tappuni, A.R.; Davis, Graham R.; Anderson, P.; Baysan, A.
Abstract: Objectives: To compare the efficacy of fluoride varnishes either casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) or bioglass particles on the severity index of root caries. Methods: Visual-tactile assessments including lesion hardness was carried out to categorise the severity index of 80 extracted teeth with primary root caries. These teeth were randomly divided into four groups; CPP-ACP and fluoride, bioglass and fluoride, fluoride only, and no treatment. Standardised toothbrushing using a dentifrice containing 1450 ppm fluoride was carried out twice a day for all groups. All samples were stored in remineralising solution at 37°C for 45 days. Visual-tactile assessments were carried out at baseline, and after 45 days. Surface roughness measurements (Ra) were performed at baseline and after 7, 14, 30 and 45 days. X-ray Microtomography was performed at the baseline and after 45 days for three samples from each group to quantify the change in mineral contents in the lesion area. Results: The Visual-tactile assessment results showed a reduction in the severity index of root caries, being 20% in CPP-ACP and fluoride, 100% in bioglass and fluoride, 80% in fluoride only, and 60% in non-varnish (toothbrushing only). Non-significant change in surface roughness was observed in all groups. X-ray Microtomography assessment showed a highly significant increase in the mineral deposition in all cases (p > .001). Conclusion: The combination of bioglass with fluoride has a potentially superior effect than either CPP-ACP with fluoride or fluoride only to reverse and arrest the root caries in a laboratory setting. Clinical significance: The combination of bioglass particles and fluoride formulation is likely to have a significant impact in reversing and arresting root caries in a minimally invasive approach. However, randomised controlled double-blinded clinical trials are required to translate these results into clinical practice.